Using ICT to Improve Teaching and Learning of Kiswahili Language for University Students - Mugaya, Tumaini Samweli (International Journal for Educational and Vocational Studies, 2020)
This study aimed to investigate the use of Information and Communication Technology (ICT) to improve Kiswahili teaching and learning at the University of Dodoma. The objectives of the study were: To identify the experience of using ICT devices in teaching general language, to examine the use of ICT in Kiswahili language classes and suggest innovative ICT tools to teach and spread Kiswahili. The study employed social learning theory of Bandura. The study used a descriptive survey design to answer the research questions. Purposive sampling was used to choose key informants. Documentaries, interviews and focus group discussion were used for teachers and students to collect data and documentary reviews used to provide further information.The results showed a limited use of ICT in teaching and learning of general languages and this adds up into poor access of existing installed language laboratory. The results also showed minimal use of ICT in Kiswahili language classes to the extent that majority of the students preferred to use Kiswahili in the computers, laptops and mobile phones. However, the study came up with various innovative ICT tools such as web based learning and improved language lab to teach and spread Kiswahili language. This can be done through ICT tools such as computer use, mobile phones and accessing the internet through language apps.